APPLICATION OF ARTIFICIAL INTELLIGENCE TOOLS AND THEIR MARKETING STRATEGIES IN DETERMINING THE TARGET AUDIENCE IN HIGHER EDUCATION INSTITUTIONS (Marketing Journal, 2025)
This study analyzes the integration of artificial intelligence technologies into the marketing strategies of higher education institutions. The role of AI tools in optimizing university operations is revealed through user segmentation, recommendation syste ms, digital communication, and the “Smart University” model. Based on an international literature review, conceptual approaches are developed and a model of AI -based personalized marketing and strategic management is proposed.
Keywords: artificial intelligence; higher education; digital marketing; segmentation; recommendation system; management; smart university